Optimalisasi Potensi Siswa SMA Saribuana Makassar dalam Menggunakan Microsoft Office - Sumandiyar, Adi; Arda (Indonesian Journal of Community Services, 2022)
This training aims to provide a technical understanding of Microsoft Office for students of SMA Saribuana Makassar. In addition, to optimize the role of the Saribuana Makassar High School teacher in providing Microsoft Office training for students. The results of the training are expected to contribute to the development of skills for students of SMA Saribuana Makassar in accessing important information regarding the operation of Microsoft Office as one of the requirements in adapting to the world of the Industrial Revolution 4.0. Learning Microsoft Office is a medium in bridging the graduates of SMA Saribuana Makassar in accessing the world of work that is ready to be used by companies, government agencies, and other social institutions that require high school graduates who are ready to adapt to information technology.